A brief history of human blood groups. - Dariush D Farhud; Marjan Zarif Yeganeh (Tehran University of Medical Sciences, 2013)
The evolution of human blood groups, without doubt, has a history as old as man himself. There are at least three hypotheses about the emergence and mutation of human blood groups. Global distribution pattern of blood groups depends on various environmental factors, such as disease, climate, altitude, humidity etc. In this survey, the collection of main blood groups ABO and Rh, along with some minor groups, are presented. Several investigations of blood groups from Iran, particularly a large sampling on 291857 individuals from Iran, including the main blood groups ABO and Rh, as well as minor blood groups such as Duffy, Lutheran, Kell, KP, Kidd, and Xg, have been reviewed.